2012
DOI: 10.3109/17453674.2012.684139
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density is associated with the onset of spontaneous osteonecrosis of the knee

Abstract: Background and purposeThe primary event preceding the onset of symptoms in spontaneous osteonecrosis in the medial femoral condyle (SONK) may be a subchondral insufficiency fracture, which may be associated with underlying low bone mineral density (BMD). However, the pathogenesis of SONK is considered to be multifactorial. Women over 60 years of age tend to have higher incidence of SONK and low BMD. We investigated whether there may be an association between low BMD and SONK in women who are more than 60 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 24 publications
1
63
1
7
Order By: Relevance
“…The high frequency of osteopenia or osteoporosis among our study population, especially in comparison to previously reported rates of osteopenia or osteoporosis in normal adult populations, supports that the impaired bone architecture along the load-bearing surfaces is likely a risk factor for insufficiency fracture [28,29]. However, the degree of abnormality (osteopenia versus osteoporosis) to predispose to fracture remains controversial [10,30]. Additionally, in our study, female gender did show a modest association with progression of FCIF to TKA.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The high frequency of osteopenia or osteoporosis among our study population, especially in comparison to previously reported rates of osteopenia or osteoporosis in normal adult populations, supports that the impaired bone architecture along the load-bearing surfaces is likely a risk factor for insufficiency fracture [28,29]. However, the degree of abnormality (osteopenia versus osteoporosis) to predispose to fracture remains controversial [10,30]. Additionally, in our study, female gender did show a modest association with progression of FCIF to TKA.…”
Section: Discussionsupporting
confidence: 59%
“…This discovery prompted a reevaluation of SONK at the femoral condyle [2,5,6]. A spectrum of femoral condylar pathology has since been proposed, with FCIF and osteonecrosis being recognized as distinct entities along this spectrum, and osteoporosis was implicated as a risk factor [2,[7][8][9][10]. Currently, there remains limited knowledge about the clinical findings and morphological abnormalities associated with femoral condyle insufficiency fractures (FCIF).…”
Section: Introductionmentioning
confidence: 99%
“…These may induce microfracture, thus leading to subcondral insufficiency fracture [2-7] the prognosis of which is thought to be dependent on the lesion as detected in the MRI [8-12], few studies with the combination of BMD and MRI have been reported [13]. In this article, we examined the cause and prognosis of our cases which were initially diagnosed as SONK by using MRI and DEXA.…”
Section: Introductionmentioning
confidence: 99%
“…Subchondral BMD (sBMD) and subchondral bone remodelling also play important roles in OA pathology 10 11. Some studies have demonstrated that knee OA was associated with lower sBMD,3 12 while another study documented that patients with high tibial sBMD had increased joint space narrowing (JSN) over 1 year 13…”
Section: Introductionmentioning
confidence: 99%